Teaching language and literature in elementary classrooms : a resource book for professional development - Popp, Marcia S. (L. Erlbaum Associates, 2005)
Helping the beginning teacher create a classroom environment that integrates literacy development with learning, this second edition identifies the major components of an integrated language program. This is a handbook for beginning educators that serves both as a text and as a resource to be carried into the first year of teaching.